Kan et samfund leve af tro? : Om forholdet mellem Romerbrevet 1,17 og luthersk tillidskultur - Stopa, Sasja Emilie Mathiasen (Dansk Teologisk Tidsskrift, 2025)
“The righteous will live by faith.” With this quote from Hab. 2:4, Paul concludes his summary of the gospel in Romans 1:17. To Paul, living by faith means trusting God’s promise of salvation and faithfully following his commandments, which express the norms of the community. In this article, I analyse Paul’s vision of a universal, trust-based community and its influence on Luther’s theology which underlines trust as the hallmark of a sound community – with God and fellow human beings. Meditating on Romans 1:17, Luther realised that rather than being a vindictive judge, God is a loving giver who initiates a mutually obliging trust relation with humans through his self-giving in Christ. Nuancing 20th century Lutheran theology’s one-eyed focus on individual righteousness, I claim that this reformatory discovery entails a new understanding of community as built around trust in God and God-given authority rather than punishment and reward. Moreover, I argue for the potential impact of this Pauline-Lutheran trust-centered notion of community on the historic development of a Danish trust culture, pointing to Grundtvig and Løgstrup as two influential Lutheran theologians who promote trust as a defining characteristic of Danish society.